2019
DOI: 10.15666/aeer/1703_70857112
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Perception and Adaptation in Nigeria’s Guinea Savanna: Empirical Evidence From Farmers in Nasarawa State, Nigeria

Abstract: Nigeria's guinea savanna produces the bulk of the food consumed in the country and climate change is adversely affecting agriculture in the area. Farmers in the area respond differently to climate change based on their perception. Yet, studies that systematically link farmers' perception on climate change to scientific data from meteorological stations are rare in Nigeria's guinea savanna. Much rarer are studies that consider the simultaneity in the adaptation decisions of the farmers. This study therefore aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
2
17
0
1
Order By: Relevance
“…Farming experience is expected to have a positive impact on adoption of climate‐resilient strategies because the more experienced farmers have better knowledge of farm management and understand the practices and technologies needed to improve production and enhance climate resilience (Onyeneke et al ; Temesgen et al ). Pond size, which represents the size of the farm business, has received considerable attention in the climate change adaptation literature and is commonly considered to have a positive impact on adaptation (Onyeneke et al ; Tarfa et al ). Adoption of technologies tends to take place earlier and more rapidly on larger farms than on smaller farms.…”
Section: Methodsmentioning
confidence: 99%
“…Farming experience is expected to have a positive impact on adoption of climate‐resilient strategies because the more experienced farmers have better knowledge of farm management and understand the practices and technologies needed to improve production and enhance climate resilience (Onyeneke et al ; Temesgen et al ). Pond size, which represents the size of the farm business, has received considerable attention in the climate change adaptation literature and is commonly considered to have a positive impact on adaptation (Onyeneke et al ; Tarfa et al ). Adoption of technologies tends to take place earlier and more rapidly on larger farms than on smaller farms.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2: Mean Annual Rainfall Pattern in Nigeria (Ishaku and Majid, 2010)It also revealed that the respondents had heard of the term climate change but did not however realize that it was a global phenomenon and thought it a local occurrence. It was further revealed that the media had very little to do with the dissemination of information as touching climate change matters as reported byTarfa et. al., (2019) in their study of climate change perception and adaptation in Nigeria"s guinea savanna.…”
mentioning
confidence: 94%
“…Although policies and agreements are being put in place to address climate change causes, households are also implementing livelihood diversification strategies. These strategies include diversification of income and activities [11][12][13][14] to reduce their vulnerability and be more resilient to climate-related shock. Migrant remittances are cited in the literature as one of the critical elements of this strategy [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%